2006
DOI: 10.1007/s00330-006-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

Multicontrast-weighted magnetic resonance imaging of atherosclerotic plaques at 3.0 and 1.5 Tesla: ex-vivo comparison with histopathologic correlation

Abstract: The purpose was to analyze magnetic resonance (MR) plaque imaging at 3.0 Tesla and 1.5 Tesla in correlation with histopathology. MR imaging (MRI) of the abdominal aorta and femoral artery was performed on seven corpses using T1-weighted, T2-weighted, and PD-weighted sequences at 3.0 and 1.5 Tesla. Cross-sectional images at the branching of the inferior mesenteric artery and the profunda femoris were rated with respect to image quality. Corresponding cross sections of the imaged vessels were obtained at autopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…10,11 MR imaging characterization of extracranial atherosclerotic plaque has been well studied and well established. [4][5][6] Several aspects of plaque structure, including size, wall thickness, integrity of the fibrous cap, and the presence of inflammation, can be assessed using MR imaging. 13,[18][19][20][21] MR imaging characteristics of the aorta and carotid arteries, including enhancement, have been shown to be associated with elevated serum markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 MR imaging characterization of extracranial atherosclerotic plaque has been well studied and well established. [4][5][6] Several aspects of plaque structure, including size, wall thickness, integrity of the fibrous cap, and the presence of inflammation, can be assessed using MR imaging. 13,[18][19][20][21] MR imaging characteristics of the aorta and carotid arteries, including enhancement, have been shown to be associated with elevated serum markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] MR imaging characterization of extracranial atherosclerotic plaque has been well studied and well established. [4][5][6] Extracranial artery inflammatory plaques have been reported to show asymmetric wall thickening with enhancement on MR imaging. 7 High-resolution vessel wall 3T MR imaging is a fairly new technique that has allowed a more detailed examination of smallsized and deeply located intracranial arteries.…”
mentioning
confidence: 99%
“…Puppini et al 45 demonstrated that MR imaging sensitivity in the detection of calcifications is 80%. As reported by Kopps et al 46 during the study of calcified plaques of the aorta and of femoral arteries, MR imaging sometimes showed signal intensity loss typical of the presence of calcifications, though after histologic examination, no calcified plaques were found (false-positive presence). Link et al 47 demonstrated that the presence of calcified plaques was correctly interpreted with DSA in only 56% of patients.…”
Section: Discussionmentioning
confidence: 63%
“…Since large FOV imaging was performed, the data presented in this study cannot be compared to currently available high-resolution protocols that are optimized with respect to spatial resolution, eg, for carotid artery plaque imaging (35,36) or diagnosis of inflammatory vessel disease such as in giant cell arteritis (37). However, the aim of this study was to analyze a protocol with a large FOV that also provides additional information during first-pass imaging on the arterial and venous vasculature where high-resolution protocols (15) are not the focus the examination.…”
Section: Discussionmentioning
confidence: 99%